Implementation of finite set model predictive current control for shunt active filter - A. Yahia Cherif; H. Laib; K. Barra (9th International in Renewable Energy Congress (IREC), 2018)
The present paper investigates the effectiveness of Finite Set Model Predictive Current Control (FS-MPCC) for Shunt Active Filter SAF and its implementation on real bench. The method uses a Multivariable Filter MVF to extract the fundamental components of currents and voltages of the grid. The predictive control method uses a cost function containing the error of the filtered currents to be controlled. The performances of the control method are revealed throw simulation and experimental results and then commented. The obtained results show that predictive control is a powerful control method for such application in term of tracking performance and quality energy.